Adapting Online Education for Deaf and Hard-of-Hearing Adults: Preferences, Perceptions, and Learning Characteristics - Yessengaliyev, Adilkazy; Karelkhan, Nursaule; Goris, Tatiana; Schmidt, Peter (International Journal of Online and Biomedical Engineering (iJOE), 2025)
This study explores the online education preferences and learning characteristics of deaf and hard-of-hearing adults based on a survey of 51 participants. Findings show that most participants prefer using smartphones to access online resources, while tablets and PCs are less favored. Respondents engage frequently with social media and news websites but use educational platforms, online banking, and government services less often. Key preferences include the use of visual components—such as sign language videos, graphics, and illustrative examples—highlighting the importance of visual learning. Additionally, clear module structures with pre- and post-lesson exercises are valued for improving comprehension. The study concludes that adaptive, mobile-friendly online courses with short, visually focused modules are essential for effective learning among individuals with hearing impairments.